Relación familia-finca de productores agropecuarios en el municipio El Salvador / Family-farm relationship of agricultural producers in the municipality of El Salvador - Sucel Batista Fonseca (Universidad de La Habana, 2020)
For Cuba it is clear that it continues to be a challenge to raise agricultural production with sustainability, therefore, it is important to study the population that carries out the projected transformations, especially the families involved in the municipalities where that economic activity is the center of your development program. The present study, as part of a broader investigation, aimed to analyze the family-farm relationship of agricultural producers associated with Credit and Service Cooperatives (CCS) in the municipality of El Salvador (May 2018 - March 2019), Guantánamo province, through the study of the family-farm life cycle and its possibilities of family replacement. Research techniques such as content analysis, structured interview, supported by descriptive statistics and multivariate analysis in SPSS Statistics 21 were combined. The family-farm relationship in the municipality of El Salvador is active, direct and diverse. Although the family replacement rate is considered high for the UFPA-CCS, there are still producers without family replacement in this municipality, with the growth and dispersion/delivery stages prevailing in the family-farm life cycle. Resumen Para Cuba queda claro que continúa siendo un desafío elevar la producción agropecuaria con sostenibilidad, por tanto, resulta importante el estudio de la población que lleva a cabo las transformaciones que se proyectan, especialmente las familias implicadas en los municipios donde esa actividad económica es centro de su programa de desarrollo. El presente estudio, como parte de una investigación más amplia, se propuso analizar la relación familia-finca de productores agropecuarios asociados a Cooperativas de Créditos y Servicios (CCS) en el municipio El Salvador (mayo 2018-marzo 2019), provincia de Guantánamo, a través del estudio del ciclo de vida familia-finca y sus posibilidades de reemplazo familiar. Se combinaron técnicas de investigación tales como el análisis de contenido, la entrevista estructurada, apoyados en la estadística descriptiva y el análisis multivariado en SPSS Statistics 21. La relación familia-finca en el municipio El Salvador se manifiesta activa, directa y diversa. Aunque se considera alto el índice de reemplazo familiar para las unidades familiares de producción agropecuaria asociadas a las Cooperativas de Créditos y Servicios (UFPA-CCS), aún existen productores sin reemplazo familiar en este municipio, con predominio de las etapas de crecimiento y dispersión/entrega en el ciclo vital familia-finca.